STUDI PENGARUH VARIASI HYDRAULIC LOADING RATE (HLR) DAN KONSENTRASI INFLUEN TERHADAP PENURUNAN BOD, COD, DAN TSS LIMBAH CAIR DOMESTIK BLACK WATER MENGGUNAKAN REAKTOR UASB - R. Reindy Ragil R (Jurnal Teknik Lingkungan, 2013)
Black water in Indonesia most still not yet been done  processing. Therefore needed the existence of a research about effectiveness processing of black water use UASB. This research, parameter to check only BOD, COD, and TSS. Parameters is based on some parameters dominant existing in waste water domestic. Variation HLR  is 0,06 m³/m²/jam, 0,04 m³/m²/jam, and 0,03 m³/m²/jam, COD concentration variation is 2347 mg / l for low concentration, 3000 mg / l for the mid concentration and 3800 mg / l for high concentration. From result of analysis got result of degradation BOD, COD, and TSS. Its Result, For the BOD degradation efficiency ranges 27,71 - 53,58%, for the COD degradation efficiency ranges 35,26 - 52,71%, and for the TSS degradation efficiency ranges 35,38 - 76,36%.